ANALISIS PEMASARAN PRODUK ABON IKAN PADA RUMAH PRODUKSI MAHAKARYA ‘CANTING’ DI PANGANDARAN - Junianto, Junianto; Zatifa, Keysa Alia; Ramadan, Rizki Yudha; Alika, Raj Surya (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
One way that can be used to use fish so that it has a long shelf life and high selling value is by processing it into fish floss. UMKM Mahakarya Canting is one of the businesses operating in the fish floss processing industry located in Pangandaran Regency, West Java. This research aims to determine added value, consumer analysis, competitor analysis, marketing planning and production/demand analysis of the Mahakarya Canting production house business. The research method used is survey.  Data was obtained through interviews and observations at company locations.  The results show that an added value of Rp. 56,286/kg with a ratio value of 62.54% which is included in the high value-added ratio category. This MSME business for fish floss products has its main target, namely Pangandaran residents, whether individuals or distributors. UMKM Mahakarya Cantig in its marketing planning, quality is an important thing to pay attention to, both in terms of product nutrition and the product's outer packaging.  As for facing competition, the canting fish floss product has a unique advantage, namely that it has its own technique to eliminate the fishy smell in its processing.